Ancillary Treatment versus Co-Amoxiclav in Bacterial Rhinosinusitis Management - Shahid Iqbal, Ikram Ullah, Muhammad Ali Ranjha, Arshad Abbas, Wajih Ud Din Shinwari, Jamshed Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Acute bacterial rhinosinusitis (ABRS) presents a clinical challenge in optimizingmanagement between antibiotic therapy and supportive (ancillary) measures. This studycompares the outcomes of ancillary treatment alone versus antibiotic therapy with Co amoxiclav in adult patients with ABRS